A dish served cold: targeting revenge in revenge pornography. (September 2019) - Dymock, Alex; van der Westhuizen, Charlotte
Abstract: The introduction of s 33 of the Criminal Justice and Courts Act 2015, criminalising the disclosure of private sexual images, has been seen as a welcome step forward for curbing this abuse of privacy and the harmful effects it has on victims. However, while s 33 sidesteps any reference to 'revenge pornography', as the phenomenon has been termed in popular vernacular, little attention has been paid to the way in which narratives of revenge implicitly underpin and imbue the new offence, particularly its specific intent requirement. We argue this has serious implications for the treatment of s 33 offences in the courts and for sentencing. Drawing on cross-disciplinary conceptualisations of revenge, its recent criminal-legal history, and examples of media and parliamentary rhetoric, we claim that despite innumerable attempts to turn debate on disclosure of private sexual images towards consent, harm and privacy, there lurks within these discourses an assumption that the victim must have done something to deserve the treatment she received. Until the multiple harms of disclosure of private sexual images are recognised and explicit recommendations are made that scrutiny of victims' behaviour should normally be inadmissible, we argue that the offence offers little in the way of redress.